2011
DOI: 10.1088/0957-4484/22/22/225603
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional distribution of carbon nanotubes in copper flake powders

Abstract: We report an approach of flake powder metallurgy to the uniform, two-dimensional (2D) distribution of carbon nanotubes (CNTs) in Cu flake powders. It consists of the preparation of Cu flakes by ball milling in an imidazoline derivative (IMD) aqueous solution, surface modification of Cu flakes with polyvinyl alcohol (PVA) hydrosol and adsorption of CNTs from a CNT aqueous suspension. During ball milling, a hydrophobic monolayer of IMD is adsorbed on the surface of the Cu flakes, on top of which a hydrophilic PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It was shown that the presence of oxygen at the Cu-CNT interface resulted in good load transfer affecting high degree of strengthening [25] in compacts obtained by spark plasma sintering. Another technique used for improving dispersion is by attaching CNTs to Cu flakes produced by ball milling by means of a binder [26]. Roll bonding has also been used for dispersing CNTs between thin Cu foils [27].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the presence of oxygen at the Cu-CNT interface resulted in good load transfer affecting high degree of strengthening [25] in compacts obtained by spark plasma sintering. Another technique used for improving dispersion is by attaching CNTs to Cu flakes produced by ball milling by means of a binder [26]. Roll bonding has also been used for dispersing CNTs between thin Cu foils [27].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with a spherical powder, the two-dimensional structures of the flake powder and of graphene are very similar, which can effectively increase the contact area between the powder and graphene. This will not only enable improved support for the GNPs but also improve the bond strength between the alloy matrix and the GNPs [ 4 , 12 , 14 , 15 ]. As can be seen in Figure 2 , due to the high rotation rate and high ball-to-powder ratio, the repeated compression impact force exerted by the ball on the powder during the ball-milling process is large, and the initially spherical Cu–Cr–Mg alloy powder particles have been flattened.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, these solutions require energy and time consumption which is incompatible with industrial production. Therefore, pre-dispersion optimized methods are fundamental in this direction [34,52,69,82]. It seems that FPM results in the best route, with optimal control of the process and high mechanical properties, even if there is still space for further improvement.…”
Section: Flake Powder Metallurgy High-shear Pre-dispersion and Ssbm (Fpm-hspd/ssbm)mentioning
confidence: 99%